Flow behaviour of Ti-6Al-4V alloy in a wide range of strain rates and temperatures under tensile, compressive and flexural loads. (April 2023) - Prakash, Gyan; Singh, N.K.; Gupta, N.K.
Highlights: Sensitivity of Ti-6Al-4V alloy under tensile, compressive and flexural loads. Effects of soaking time and heating rate on the mechanical properties of the alloy. Fractography analysis of fractured tensile specimens using scanning electron microscope. Dependency of material properties on specimen geometry and, the assessment of ductility and toughness/energy dissipation at different strain rates. Applicability of Cowper-Symonds (CS) and Johnson-cook (JC) models for Ti-6Al-4V alloy under various loading conditions. Abstract: The design and analysis of lightweight structures subjected to impact loads require detailed understanding of impact phenomena, and dynamic responses of the selected materials for their safety and reliability. Titanium alloys are in demand for such structures due to high strength to weight ratio, high toughness, and the ability to withstand extreme temperatures. Therefore, this paper investigates the flow behaviour of the titanium alloy Ti-6Al-4V under tensile, compressive and flexural loads at different strain rates and temperatures. Quasi-static tests are performed under tension and compression at strain rates 0.0001–0.1 s −1 while flexural (three-point bending) tests at crosshead speeds 1–100 mm/min are conducted for 90–150 mm span lengths with varying specimen orientations (flat and transverse) on electromechanical universal testing machine (UTM) at room temperature 25 °C. High temperature (300–700 °C) experiments are performed on this UTM under tensile strain rate 0.001s −1 where, the effects of soaking time (5–25 min) and heating rate (10–50 °C/min) are studied. Superplastic behaviour of the alloy is observed at temperature 700 °C with maximum engineering strain nearly 200%. High strain rate experiments on split Hopkinson tension bar (SHTB) and split Hopkinson pressure bar (SHPB) setups are conducted under tension with strain rates 850–1150 s −1, and compression with strain rates 1100–2300 s −1, respectively at room temperature. Ductility and toughness (energy dissipation) are determined at different loading rates. The dependency of the material properties is observed on specimen geometry. Fractography analysis is done for fractured tensile specimens by scanning electron microscope (SEM), and thereafter, existing Cowper-Symonds (CS) and Johnson-Cook (JC) material models are evaluated for the alloy based on the experimental data obtained at different loading conditions.